Silver-based diamond composites with highest thermal conductivity. Issue 2 (1st April 2012) - Weber, Ludger; Tavangar, Reza
Abstract : Composites are produced based on diamond particles having monomodal or mixtures with bimodal size distribution contained in silver-based alloys. The composites were produced by gas pressure-assisted liquid metal infiltration with the aim to maximize thermal conductivity. The diamond content ranged between 60 and 79 vol.-pct. Thermal conductivities slightly above room temperature reached values close to 1000 W/m/K, that is, 2·5 times the thermal conductivity of pure copper at the same temperature. Experimental data are confronted to a modified Differential Effective Medium approach treating the large particles as embedded in a composite matrix consisting of Ag alloy and small particles, yielding general good agreement. Potential ways to achieve even higher thermal conductivities are discussed based on the established predictive capacity of the model presented here. It is suggested that increasing the effective thermal conductivity of the diamond particles by increasing the intrinsic thermal conductivity, the size, as well as the interface thermal conductance between diamond and the metal is the direction with highest potential, whereas modifying the diamond particle packing and the thermal conductivity of the metal are expected to be less efficient. Composites are produced based on diamond particles having monomodal or mixtures with bimodal size distribution contained in silver-based alloys. The composites were produced by gas pressure-assisted liquid metal infiltration with the aim to maximize thermal conductivity. The diamond content ranged between 60 and 79 vol.-pct. Thermal conductivities slightly above room temperature reached values close to 1000 W/m/K, that is, 2·5 times the thermal conductivity of pure copper at the same temperature. Experimental data are confronted to a modified Differential Effective Medium approach treating the large particles as embedded in a composite matrix consisting of Ag alloy and small particles, yielding general good agreement. Potential ways to achieve even higher thermal conductivities are discussed based on the established predictive capacity of the model presented here. It is suggested that increasing the effective thermal conductivity of the diamond particles by increasing the intrinsic thermal conductivity, the size, as well as the interface thermal conductance between diamond and the metal is the direction with highest potential, whereas modifying the diamond particle packing and the thermal conductivity of the metal are expected to be less efficient.